2014
DOI: 10.1186/1745-6215-15-99
|View full text |Cite
|
Sign up to set email alerts
|

The Stroke Oxygen Study (SO2S) - a multi-center study to assess whether routine oxygen treatment in the first 72 hours after a stroke improves long-term outcome: study protocol for a randomized controlled trial

Abstract: BackgroundMild hypoxia is common in stroke patients and may have significant adverse effects on the ischemic brain after stroke. The use of oxygen treatment is rapidly increasing in European stroke units but is not without side effects. It impedes early mobilization, could pose an infection risk, and may encourage the formation of toxic free radicals, leading to further damage to the ischemic brain. In the Stroke Oxygen Pilot Study (2 or 3 L/min for 72 hours) neurological recovery at one week was better in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…At 6 months [83] there was no statistically significant difference between the two groups, although there remained a small trend towards overall benefit with supplemental oxygen. This data led to the Stroke Oxygen Study (SO 2 S) [84], in which 8003 patients within 24 h of hospital admission with acute stroke were randomized 1:1:1 to receive either continuous supplemental oxygen, supplemental oxygen only at night (9pm–7am) oxygen, or no supplemental oxygen treatment for 72 h. This study has completed recruitment and is expected to report in 2016.…”
Section: Oxygen Therapy For Acute Strokementioning
confidence: 99%
“…At 6 months [83] there was no statistically significant difference between the two groups, although there remained a small trend towards overall benefit with supplemental oxygen. This data led to the Stroke Oxygen Study (SO 2 S) [84], in which 8003 patients within 24 h of hospital admission with acute stroke were randomized 1:1:1 to receive either continuous supplemental oxygen, supplemental oxygen only at night (9pm–7am) oxygen, or no supplemental oxygen treatment for 72 h. This study has completed recruitment and is expected to report in 2016.…”
Section: Oxygen Therapy For Acute Strokementioning
confidence: 99%
“…These trials compared low-flow (2-3 L/min) oxygen supplementation to room air delivered from 24 to 72 h after ischemic or hemorrhagic stroke and provided inconclusive results [13,14]. The phase III Stroke Oxygen Study (N = 8000) with a similar objective [15] showed no benefit ofbut also no safety issues withlow-flow supplemental oxygen (results presented at the 23rd European Stroke Conference 2014 in Nice, France).…”
Section: Current Clinical Evidencementioning
confidence: 99%
“…Certainly, a recent randomized controlled trial that investigated the effects of high flow (30-45 l per minute) NBO (100%) given to acute stroke patients for 8 h was terminated early due to excess mortality in the NBO group when compared to the group on air/low flow oxygen (40% versus 17%) (Singhal et al, 2014). However, preliminary findings from the largest NBO stroke trial to date, found no benefit with lower concentrations of NBO (24-32%) given up to 72 h in 8000 acute stroke patients (Roffe et al, 2014a(Roffe et al, , 2014b. Thus medium concentrations of 61% NBO may be safer and better tolerated by acute stroke patients than high NBO concentrations, but are possibly more effective than lower NBO concentrations at reducing short-term neurological impairment.…”
Section: Discussionmentioning
confidence: 93%